Ultrasonic measurement of blubber thickness in right whales - Moore, M. J.; Miller, C.A.; Arthur, R.; Lange, W.A.; Prada, K.G.; Marx, M.K.; Frey, E.A. (J. Cetacean Res. Manage., 2020)
The right whale population in the northwestern Atlantic appears to face the risk of extinction: ship and fishing gear trauma are significant mortality factors, but calving rates are also depressed compared to southern right whales. A major factor in calving success in many species is body condition. Knowledge of the dynamics of body condition is also important in studies of juvenile and sub-adult growth and seasonal changes in adults. This paper describes a method to assess body condition in live right whales. To characterise the acoustic properties of the blubber/muscle interface we first studied samples of Atlantic white-sided dolphin and right whale in the laboratory. Tissue heterogeneity was examined grossly and in histological sections. Acoustic echoes were strong from the sub-dermal connective tissue sheath(s). Echo strengths did not appear to vary with lipid content. We then used a 0.5MHz ultrasound transducer on a cantilevered 12m pole to touch the back of surfacing right whales briefly. Multiple laboratory and field measurements on individual animals suggest repeated measures of blubber thickness at a single location are reasonably consistent. Data will be normalised to both sampling position on the body and to length of the animal, estimated by mensuration from stereo video images of the animal during sampling. In this way, using a long-term consistent database of blubber thickness measurements, and catalogued reproductive histories from on-going photographic identification studies, we plan to assess the significance of changing body condition in right whale population dynamics.